Six-year analysis of traumatic injuries of the craniomaxillofacial area: relation between maxillofacial and traumatic brain injuries - Shumynskyi Євген Валерійович; Kopchak Андрій Володимирович (Actual Dentistry, 2021)
Summary. Craniofacial trauma is one of the most difficult types of injuries. There is disagreement among various authors about the relationship between maxillofacial trauma (MFT) and traumatic brain injury (TBI). Purpose. Retrospectively evaluate the epidemiology of traumatic injuries of the craniomaxillofacial area and determine whether there is a relationship between different isolated or combined fractures of the facial bones and brain damage. Materials and methods. The case histories of three groups of patients with isolated fractures of the mandible (I group), isolated fractures of the midface zone (II group) and combined fractures of all areas of the face (III group), who were hospitalized in the period from 2012 to 2017, were analyzed. The main epidemiological indicators were determined. The analysis of indicators of severity of MFT and TBI is carried out. Correlation analysis of indicators, analysis using the Kruskal- Wallis test and Steel-Dwass test for pairwise comparisons was performed. Results. Were treated519 patients. 457 men (88 %) and 62 women (12 %). The main causes of injuries were assaults (40 %). Correlation analysis did not reveal the dependence of MFT and TBI. The difference in severity of isolated fractures of the mandible and midface bones was statistically significant, and there is a statistical significance between the severity of TBI in case of isolated fractures of midface bones and panfacial fractures (p < 0.05). Conclusions. The severity of maxillofacial trauma in the case of panfacial fractures is on average 3 times higher than in the case of isolated fractures of the lower jaw or midface bones. The severity of TBI is largely consistent with concussion in all groups, but in the group with panfacial fractures, the median rate is lower comparing to other groups.